Radar cross‐section measurement in millimetre‐wave for passive millimetre‐wave identification tags. Issue 15 (1st December 2015) - Hotte, David; Siragusa, Romain; Duroc, Yvan; Tedjini, Smail
Abstract : The passive millimetre‐wave identification (MMID) technology was introduced few years ago, exploiting the advantages of the passive ultra‐high frequency (UHF) radio frequency identification (RFID). The communication is based on backscattering modulation, related to the radar cross‐section (RCS) of the transponder. Thus, the need of accurate RCS measurement in the V‐band arises. This work presents two methods to measure the RCS of any antenna in the particular case of MMID from 57 to 66 GHz. The studied methods require some precautions in millimetre‐wave compared with measurements done in the UHF band. The two approaches highlight the methodology for accurate RCS measurement while the methods are evaluated through an example. A horn antenna is used as a MMID tag antenna and the RCS of the antenna is studied across three different loads as in UHF RFID: the short circuit, the open circuit and the matched load. The proposed methods provide a good accuracy and are validated by comparing the measurement results to the simulation.